Heterocellular Contacts with Mouse Brain Endothelial Cells Via Laminin and α6β1 Integrin Sustain Subventricular Zone (SVZ) Stem/Progenitor Cells Properties - Rosa, Alexandra I.; Grade, Sofia; Santos, Sofia D.; Bernardino, Liliana; Chen, Thomas C.; Relvas, João; Hofman, Florence M.; Agasse, Fabienne (Frontiers in Cellular Neuroscience, 2016)
Neurogenesis in the subventricular zone (SVZ) is regulated by diffusible factors and cell-cell contacts. In vivo, SVZ stem cells are associated with the abluminal surface of blood vessels and such interactions are thought to regulate their neurogenic capacity. SVZ neural stem cells have been described to contact endothelial-derived laminin via α6β1 integrin. To elucidate whether heterocellular contacts with brain endothelial cells (BEC) regulate SVZ cells neurogenic capacities, cocultures of SVZ neurospheres and primary BEC, both obtained from C57BL/6 mice, were performed. The involvement of laminin-integrin interactions in SVZ homeostasis was tested in three ways. Firstly, SVZ cells were analyzed following incubation of BEC with the protein synthesis inhibitor cycloheximide (CHX) prior to coculture, a treatment expected to decrease membrane proteins. Secondly, SVZ cells were cocultured with BEC in the presence of an anti-α6 integrin neutralizing antibody. Thirdly, BEC were cultured with β1 -/- SVZ cells. We showed that contact with BEC supports, at least in part, proliferation and stemness of SVZ cells, as evaluated by the number of BrdU positive (+) and Sox2+ cells in contact with BEC. These effects are dependent on BEC-derived laminin binding to α6β1 integrin and are decreased in cocultures incubated with anti-α6 integrin neutralizing antibody and in cocultures with SVZ β1-/- cells. Moreover, BEC-derived laminin sustains stemness in SVZ cell cultures via activation of the Notch and mTOR signaling pathways. Our results show that BEC/SVZ interactions involving α6β1 integrin binding to laminin, contribute to SVZ cell proliferation and stemness.